Obstructed giant right paraduodenal hernia presenting as an abdominal mass - Zachariah, Sanoop Koshy; Rajeeve, Sridevi (International Surgery Journal, 2018)
Internal hernias are rare cases of small intestinal obstruction of which Right Paraduodenal hernias through the Fossa of Waldeyer occur only in less than a quarter of all cases. A high index of suspicion and a good understanding about the pathological anatomy is pertinent for the detection and successful management of this condition which has non-specific symptomatology. The gold standard of diagnosis is computed tomography scan, which shows characteristic findings. Surgical correction is often necessary as mortality rates hover above 50% in unintervened cases. Here we present very rare case of an obstructed right paraduodenal hernia which presented as an abdominal mass.